UJI EFEK ANALGESIK EKSTRAK ETANOL DAUN KERSEN (Muntingia calabura L.) PADA MENCIT PUTIH JANTAN (Mus musculus) DENGAN INDUKSI NYERI ASAM ASETAT - Triswanto Sentat; Susiyanto Pangestu (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2016)
Kersen leaf (Muntingia calabura L.) contains tannins, flavonoids and polyphenol compounds allegedly have analgesic effect. The objective was to determine the analgesic effect of ethanol extract of kersen leaves and to determine the most effective analgesic dose. This study was an experimental research. Leaves were extracted with ethanol 70% and the analgesic effect test was divided into 5 groups: negative control treatment (distilled water), positive control (mefenamic acid 2.6mg/kg), kersen leaf ethanol extract first dose (100mg/kg), second dose (200mg/kg) and tthird dose (400mg/kg). Giving treatments by oral, after 30 minutes, the mices were given a pain inductor with 0.5% acetic acid by intra peritonial administration. Analgesic power was calculated by counting the number of writhing in mice for 1 hour. The results showed that the ethanol extract of cherry leaf has analgesic effect. From the calculation of the first dose analgesic power (42.9%), second dose (59.4%) and the third dose 69.9%. Statistical test results kruskal wallis value of p=0.011 (p<0.05) showed a significant difference between all analgesic treatment groups. The conclusion of this study is all of the ethanol extract had analgesic effects on male white mice, whereas a dose of 400mg/kg is the most effective analgesic dose.